Biodiesel production : feedstocks, catalysts and technologies - Rokhum, Samuel Lalthazuala; Halder, Gopinath; Assabumrun, Suttichai; Ngaosuwan, Kanokwan (Wiley, 2022)
"This book discusses recent progress, challenges and current trends in biodiesel production. It highlights various feedstocks, emphasizing their advantages and disadvantages from diverse perspectives, and discusses different catalysts that have been used in the preparation of biodiesel, their synthesis, reactivity, recycling techniques, and stability. The effects of each catalyst?s morphology, surface area and nature of bonding on the yield of biodiesel are addressed. Recently developed technologies for sustainable production of biodiesel are presented and the book concludes with a discussion on sustainability, commercialization and future prospects for biodiesel production. Topics covered include:? Biodiesel feedstocks: Edible and non-edible oils, waste cooking oil, microalgae and animal fats that can be produced from renewable resources.? Catalysts used in biodiesel production: Homogeneous catalysts, metal oxides, supported metal oxides, mixed metal oxides, nanocatalysts, resin supported catalysts, bifunctional catalysts, catalysts derived from renewable resources, enzymatic biodiesel production, ionic liquids, metal organic frameworks.? Technologies, byproduct valorization, and future prospects of biodiesel production:: Upstream, mainstream and downstream strategies, Valorization of bioglycerol to value-added chemicals, sustainability, commercialization and future prospects of biodiesel production"-- Provided by publisher
Keywords: Biodiesel fuels.; elektronické knihy; electronic books